Efficacy of Copper Alternatives to Control Citrus Canker (Xanthomonas citri pv. citri) in Acid Lime - Katuwal, Amrit; Acharya, Umesh Kumar (Journal of the Plant Protection Society, 2024)
Citrus canker, caused by Xanthomonas citri pv. citri, is a widely occurring destructive bacterial disease of citrus, especially of acid lime (Citrus aurantifolia). Copper-based pesticides are widely used to control this disease, and their multiple and continuous applications not only cause toxicity to the plant but also induce resistance to bacteria. Therefore, this study was conducted to evaluate the efficacy of alternative antibiotics. The foliar spray was done to twelve-year-old acid lime variety Sunkagati-2 during July-September in 2023. Streptomycin sulphate + tetracycline hydrochloride, validamycin A, kasugamycin and zinkicide were compared with Bordeaux mixture and copper oxychloride. A randomized complete block design was assigned to three replications of each of the seven treatments. Bordeaux mixture had the least disease severity on leaves with a mean value of 11.75 ± 1.13%. Streptomycin sulphate + tetracycline hydrochloride, which had the second-lowest disease severity (14.96 ± 1.61%), was statistically similar to Bordeaux mixture. Similarly, validamycin A (21.54 ± 2.84%) and kasugamycin (21.75 ± 3.2%) also showed some level of effectiveness. Streptomycin sulphate + tetracycline hydrochloride showed the lowest size of lesion on leaves (3.09 ± 0.4 mm). The results of this study showed that streptomycin sulphate + tetracycline hydrochloride and validamycin A could be substituted for copper-based compounds. Further research on the effectiveness of these bactericides and their effect on plant toxicity and bacterial resistance is required to validate these results.